S-15176 Difumarate Salt Can Impair Mitochondrial Function through Inhibition of the Respiratory Complex III and Permeabilization of the Inner Mitochondrial Membrane - Natalia V. Belosludtseva; Vlada S. Starinets; Alena A. Semenova; Anastasia D. Igoshkina; Mikhail V. Dubinin; Konstantin N. Belosludtsev (Biology, 2022)
S-15176 difumarate salt, a derivative of the anti-ischemic metabolic drug trimetazidine, has been intensively studied for its impact on cellular metabolism in animal models of ischemia-reperfusion injury of the liver, heart, spinal cord, and other organs. Despite evidence of some reduction in oxidative damage to cells, the results of therapy with S-15176 have been mostly disappointing, possibly because of the lack of data on its underlying mechanisms. Here, we aimed to investigate in more detail the role of complexes I-IV of the electron transport chain and membrane permeability transition in mitochondrial toxicity associated with S-15176. Using rat thymocyte and liver mitochondria, we demonstrated that: (1) acute exposure to S-15176 (10 to 50 μM) dose-dependently decreased the mitochondrial membrane potential; (2) S-15176 suppressed the ADP-stimulated (State 3) and uncoupled (State 3UDNP) respiration of mitochondria energized with succinate or malate/glutamate, but not ascorbate/TMPD, and increased the resting respiration (State 4) when using all the substrate combinations; (3) S-15176 directly inhibited the activity of the respiratory complex III; (4) low doses of S-15176 diminished the rate of H2O2 production by mitochondria; (5) at concentrations of above 30 μM, S-15176 reduced calcium retention capacity and contributed to mitochondrial membrane permeabilization. Taken together, these findings suggest that S-15176 at tissue concentrations reached in animals can impair mitochondrial function through suppression of the cytochrome bc1 complex and an increase in the nonspecific membrane permeability.